Taxonomy and nomenclature in palaeopalynology: basic principles, current challenges and future perspectives. (2nd October 2021) - Gravendyck, Julia; Fensome, Robert A.; Head, Martin J.; Herendeen, Patrick S.; Riding, James B.; Bachelier, Julien B.; Turland, Nicholas J.
Abstract: Effective communication of taxonomic concepts is crucial to meaningful application in all biological sciences, and thus the development and following of best practices in taxonomy and the formulation of clear and practical rules of nomenclature underpin a wide range of scientific studies. The International Code of Nomenclature for algae, fungi and plants (the Code ), currently the Shenzhen Code of 2018, provides these rules. Although early versions of the Code were designed mainly with extant plants in mind, the Code has been increasingly used for fossil plants and, in recent decades, for organic-walled microfossils, the study of which is called palaeopalynology, or simply palynology. However, rules embodied in the Code do not fully reflect the needs and practices of this discipline; and taxonomic practices between fossil applications, especially in palynology, have tended to diverge from practices for extant plants. Differences in these rules and practices present specific challenges. We therefore review the Shenzhen Code as it applies to palynology, clarifying procedures and recommending approaches based on best practices, for example, in the designation and use of nomenclatural types. The application of nomenclatural types leads to taxonomic stability and precise communication, and lost or degraded types are therefore problematic because they remove the basis for understanding a taxon. Such problems are addressed using examples from the older European literature in which type specimens are missing or degraded. A review of the three most important conventions for presenting palynological taxonomic information, synonymies, diagnoses/descriptions and illustrations, concludes with recommendations of best practices. Palynology continues to play an important role in biostratigraphy, palaeoenvironmental analyses, and evolutionary studies, and is contributing increasingly to our understanding of past climates and ocean systems. To contribute with full potential to such applied studies, consistent communication of taxonomic concepts, founded upon clear rules of nomenclature, is essential.